IMPLEMENTATION OF THE PRINCIPLE OF PUBLIC PARTICIPATION IN ARRANGEMENT OF STREET TRADERS - Shandy Herlian Firmansyah; Nanik Prasetyoningsih; Moh. Lubsi Tuqo Romadhan (Faculty of Law, Universitas Pekalongan, 2023)
This research is included in the type of juridical empirical legal research (sociological). Empirical juridical research is a type of research that uses and processes empirical facts taken from human behavior, both verbally which can be obtained through interview techniques and real behavior obtained by direct observation. To obtain this research material, the researcher uses the literature study method, namely by studying legal materials and by conducting field studies that examine the facts in the field. While the legal material in this study is library material in the form of primary legal material, legal and non-legal articles and books as secondary legal material and the results of interviews in the field as tertiary legal material